Analysis of the Implementation of the Digitalization of Non-Communicable Disease Screening Reporting Policy Through the ASIK Aplication - Hadid Al Hafidz Hafidz; Kodrat Pramudho; Maya Natalia Manan (Indonesian Journal of Global Health Research, 2026)
Aplikasi Sehat IndonesiaKu (ASIK) is a digital-based healthcare service recording and reporting application aimed at replacing manual recording and simplifying the reporting process for various health programs. Field experience shows that there is still a gap between the reporting results in the application and manual recording, resulting in serious consequences for the validity of health data. This study aims to evaluate the implementation of the digitalization policy for reporting non-communicable disease screening through the ASIK application in North Lampung Regency in 2025. The evaluation was conducted by examining four main factors, namely the technical aspects of the application, human resources, organizational support, and health accessibility. This research uses a qualitative approach with a case study design using triangulation methods in the form of in-depth interviews, observation, and documentation. Data were collected through in-depth interviews, document review, and field observations at primary health facilities, and analyzed thematically using triangulation of sources and methods. Barriers to ASIK reporting are a multidimensional problem that causes a gap between policy design and field readiness. The research results show four main factors causing low reporting, namely technical application factors, limited human resources, weak organizational support, and regional accessibility constraints. This study recommends integration and strengthening of the ASIK system, improved infrastructure support and reporting management in the regions, and further quantitative studies to assess its impact on the quality of NCD screening data.